General massive one-loop off-shell three-point functions - Suzuki, A. T.; Santos, E. S.; Schmidt, AGM (Iop Publishing Ltd, 2003)
In this work we compute the most general massive one-loop off-shell three-point vertex in D-dimensions, where the masses, external momenta and exponents of propagators are arbitrary. This follows our previous paper in which we have calculated several new hypergeometric series representations for massless and massive (with equal masses) scalar one-loop three-point functions, in the negative dimensional approach.